2023
DOI: 10.1039/d3tb01094e
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-sensitive mesoporous nanoparticles loaded with cinnamaldehyde for chemodynamic and immunological therapy of cancer

Abstract: Chemodynamic therapy as a novel type of chemotherapies can damage the DNA structures and induce cell apoptosis and immunogenic cell death (ICD) through generating reactive oxygen species (ROS) to aggravate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent experiment has shown that lipid microparticles have a similar potential to lipid nanostructures to deliver mRNA and impair the progression of cancer [ 47 ]. Moreover, an improvement in the cancer therapy has been obtained through application of stimuli-responsive nanocarriers such as glutathione-responsive mesoporous nanostructures that active both immune system and mediate chemotherapy in the tumor suppression [ 48 ]. Since the potential of chemotherapy in the suppression of tumor has been reduced that the main reason is the development of resistance, the application of nanostructures such as micellar nanostructures for the delivery of chemotherapy compounds has improved the potential in tumorigenesis suppression [ 49 ].…”
Section: Nanoparticles In Tumor Therapymentioning
confidence: 99%
“…Interestingly, a recent experiment has shown that lipid microparticles have a similar potential to lipid nanostructures to deliver mRNA and impair the progression of cancer [ 47 ]. Moreover, an improvement in the cancer therapy has been obtained through application of stimuli-responsive nanocarriers such as glutathione-responsive mesoporous nanostructures that active both immune system and mediate chemotherapy in the tumor suppression [ 48 ]. Since the potential of chemotherapy in the suppression of tumor has been reduced that the main reason is the development of resistance, the application of nanostructures such as micellar nanostructures for the delivery of chemotherapy compounds has improved the potential in tumorigenesis suppression [ 49 ].…”
Section: Nanoparticles In Tumor Therapymentioning
confidence: 99%
“…According to a 2015 study by Bae et al, CA has anti-angiogenic activity, which is partly regulated by the mammalian target of rapamycin (mTOR) pathway-mediated inhibition of HIF-1 α protein expression [ 88 ]. Other studies have demonstrated that CA suppresses the expression of vascular endothelial growth factor (VEGF) and HIF- α in cancerous tissues, effectively impeding melanoma progression [ 89 ]. This inhibition consequently inhibits the proliferation and migration of vascular endothelial cells, thereby preventing the formation of new blood vessels [ 90 ].…”
Section: The Role Of Cinnamaldehyde In Cancer Preventionmentioning
confidence: 99%
“…To improve the therapeutic efficacy of CDT, one of the alternative approaches is to combine CDT with specific stimulators or anticancer drugs [13,14]. Several compounds such as camptothecin (CPT), purpurin and cinnamaldehyde have been proved to upregulate the intracellular reactive oxygen species (ROS) [15][16][17]. The upregulation of ROS can not only provide high concentration of H 2 O 2 for CDT, but also deplete reducing substances such as glutathione (GSH) to destroy the redox balance within tumor cells [18,19].…”
Section: Introductionmentioning
confidence: 99%